Analysis of architectural planning in the Middle Horizon: A view from the Wari enclaves of Wiracochapampa (La Libertad) and Pikillaqta (Cusco) - Sulca Huarcaya, Nils Ramiro (2022)
The Wari society (600 AD-1000 AD), reflected a fundamental socio-political change in the Andean territory, developing innovative architectural planning techniques of great relevance for understanding the nature of its expansion, Wiracochapampa and Pikillaqta, were a reflection of the installation of Imperial rule at two ends of the territory. The similarity of the architectural pattern of both, suggests that they would have been built by a regulatory apparatus, where instruments such as architectural models in ceramics, symbolic representations in textiles and even quipus were possibly used.